The Role of Service Quality Dimensions in the Brand Equity of the Iranian Football Clubs Based on the SERVQUAL Model - Mojtaba Salari; َAkbar Jaberi; Koorosh Ghahreman Tabrizi (Archives in Sport Management and Leadership)
Given the importance of service quality in the development of sports brands, the overall purpose of this study was to study the role of service quality dimensions in the brand equity of the Iranian football clubs based on the SERVQUAL model. The study was a descriptive-survey research and a practical one. The research population consisted of all football fans in Iranian Premier League who had experience of attending in their favorite team stadium. Due to the lack of accurate and reliable statistics of the number of fans, the statistical sample was calculated using Cochran's formula. Using available purposive sampling, 210 fans were surveyed as the research sample. Data were collected using Brand Equity Questionnaire developed by Yoo and Donthu (2001) and SERVQUAL questionnaire developed by Jaberi et al. (2013). Eight experts in the field of sports management and marketing confirmed the face and content validity of the research tools. The reliability of the research tools were verified based on Cronbach's alpha. Structural equation modeling was used to test the research hypotheses. According to the research findings, service quality had a positive and significant effect on brand equity of Iranian Premier League clubs. The results showed that service quality components (Tangibles, Reliability, Responsiveness, Assurance, and Empathy) had a significant and positive effect on brand equity of football clubs in Iranian Premier League. According to research findings, promoting and improving the service of Iranian football clubs can play a key role in developing their brand equity.